Sécurité Alimentaire en Tunisie : Des Eléments de Contexte - Gharbi, Ines; Darghouth, Mohamed Aziz; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2024)
The agricultural sector of Tunisia is confronted with considerable challenges, stemming from vulnerabilities related to climate, economy, society, and health. These challenges have led to diminished productivity, thereby eroding economic, social, and environmental efficiency. In response to these challenges, there is an urgent need for a new national positioning that is supported by a comprehensive diagnosis of current and future dynamics. This new positioning must better guide long-term strategies and actions for the sustainable development of agri-food systems. This brief underscores the present interplay and prospects of geopolitical and economic pressures, demographic and social dynamics, global market dependencies, climate change risks, and farmland degradation. These elements have a substantial impact on food security and necessitate a strategic reorientation toward greater resilience and sustainability. This document offers a synopsis of these pivotal contextual elements, intended as an introduction to more exhaustive foresight studies and strategies.